Motivation and Anxiety in English Language Classrooms at Intermediate level in Daska, Sialkot, Pakistan - Mubashar Raza (University of Chitral Journal of Linguistics and Literature, 2019)
Positive motivation plays an important role in the acquisition of L2 at all levels. The present study tries to explore why 70% Sialkoti students enrolled in public schools (School Education Department Punjab 2020,April 20) are not interested in English language and as a result Pakistan is suffering both in terms of economy and progress. In the past, researchers ignored the factors such as anxiety, absence of motivation and socio-Economic factors that affect motivation. The research shows that Sialkoti students having strong economic background show keen interest in English language learning as compared to those with poor or weak economic background. Poor economic conditions cause discomfort, low or no interest in the classroom, weaker student-teacher bond and absence of selfrespect. These conditions increase the level of anxiety and demotivate the learner to speak English in the classroom. It is very important to maintain conducive environment for the students so that they may pay more attention to the acquisition of language. The population of this research consists of 56 intermediate students of Govt. Higher Secondary School Adamkay Cheema, Sialkot. The researcher formulated a questionnaire on lickert’s scale and provided maximum time to the students to solve it. The data has been analyzed using SPSS version 22.0. The results of the study show that motivation plays a very important role in learning L2 in students of Daska, Sialkot.